2009
DOI: 10.1111/j.1467-789x.2009.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of the prevalence of childhood overweight and obesity in Italy

Abstract: To estimate the prevalence of childhood overweight and obesity among Italian schoolchildren and to examine geographic differences and present and future implications for health care, we used data from a nationwide representative survey performed in May 2008 among third-grade students in 18 of Italy's 21 regions. Cluster sampling was used to identify classes for participation. The study population included all children aged 8-9 years whose parents agreed to opt-out consent. Parents, children and teachers comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
61
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 16 publications
(18 reference statements)
14
61
4
2
Order By: Relevance
“…In fact, the results showed a higher prevalence of overweight/obesity in those adolescents whose mothers were housemakers compared to those whose mothers were employed. These findings contrast with previous studies on younger children, which pointed out the opposite effect (34,35) but are in agreement with the results of the Italian survey conducted on younger children (36).…”
Section: Discussioncontrasting
confidence: 57%
“…In fact, the results showed a higher prevalence of overweight/obesity in those adolescents whose mothers were housemakers compared to those whose mothers were employed. These findings contrast with previous studies on younger children, which pointed out the opposite effect (34,35) but are in agreement with the results of the Italian survey conducted on younger children (36).…”
Section: Discussioncontrasting
confidence: 57%
“…[18][19][20] However, in Italy, obesity prevalence is almost twice as high, particularly in the southern region. 21 It therefore comes as no surprise that most primary care physicians in our survey agreed that childhood obesity management is relevant for primary care and that the highest rates were reported among the Italian physicians.…”
Section: Discussionmentioning
confidence: 61%
“…[3][4][5][6] Furthermore, health is strongly related to socioeconomic status and studies have shown that children of parents with a lower education have the highest risk of overweight and obesity. 7,8 Aggregated area level information can be used as a proxy for socioeconomic status when individual data is not available. 9 In our previous study, the urban-rural gradient in overweight and obesity was explained by the area education level, 2 but it is likely that it reflects environmental, cultural and individual lifestyle differences.…”
Section: Introductionmentioning
confidence: 99%